The primary lumbar hernia with multiple defects: a rare case - Lavudya, Gopisingh; Sainatham, Chiranjeevi; Komarapu, Lekha; Ramavath, Krishna; Mohankumar, Harshitha Rani Hassan; Sreepadagh, Nuthan (International Surgery Journal, 2021)
Lumbar hernia is a rare entity of abdominal wall hernia. Due to varied presentation it poses a challenge in diagnosis and management to attending surgeon. The requirement of preoperative imaging and clinical examination has indispensable role in the diagnosis and surgical (open or laparoscopic) approach is the only treatment option. We are presenting a case of 44 year old male, diagnosed as lumbar hernia with multiple defects and successfully managed by laparoscopic mesh hernioplasty. The primary lumbar hernia is a rare entity that a surgeon may encounter once in his lifetime making it an interesting surgical challenge. The adequate knowledge of preoperative imaging and anatomy are indispensable. With advances in minimally invasive surgery, it can be applied to patients with lumbar hernia and management requires a more tailored approach. This condition can be managed by laparoscopic approach successfully.